2022
DOI: 10.3390/catal12091068
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Two-Phase Catalytic System in Enantioselective Biotransformation of Racemic Atenolol

Abstract: There are several methods that allow enantiomerically pure compounds to be obtained. In the study presented herein, the enantioselective biotransformations of (R,S)-atenolol were performed with the use of various catalytic systems containing ionic liquids and toluene as a reaction medium, vinyl acetate as an acetylating agent as well as lipases from Candida rugosa. The conducted studies profs that, the use of the two-phase reaction system enables the reuse of the biocatalyst in another cycle and allows to achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Since the biocatalysts can be easily separated from the substrate and the product, the lipase can be reused in another reaction. This approach has been comprehensively described elsewhere in kinetic resolutions of various racemic compounds using ionic liquids [ 29 , 48 , 49 ]. Furthermore, it should be emphasized that the solubility of racemic clopidogrel carboxylic acid in organic solvents is relatively low and requires more significant volumes of the reaction medium, which could have a negative impact on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Since the biocatalysts can be easily separated from the substrate and the product, the lipase can be reused in another reaction. This approach has been comprehensively described elsewhere in kinetic resolutions of various racemic compounds using ionic liquids [ 29 , 48 , 49 ]. Furthermore, it should be emphasized that the solubility of racemic clopidogrel carboxylic acid in organic solvents is relatively low and requires more significant volumes of the reaction medium, which could have a negative impact on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Sikora et al reported in 2020 the kinetic resolution of racemic atenolol catalyzed by lipase from Candida rugosa with isopropenyl acetate as the acyl donor, resulting in the acetate of ( S )-atenolol in 94% ee . The authors present no evidence of the absolute configuration of this acetate, nor of the unreacted ( R )-atenolol [ 11 , 12 ]. The authors have previously published several articles on lipase catalyzed kinetic resolution of racemic atenolol with the amide of ( S )-atenolol presented as the acetate [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these methods rely on the use of toxic or expensive unusual catalysts [ 9 , 10 , 11 , 12 , 13 ], Volatile Organic Compound (VOC)-based harmful solvents [ 9 , 10 , 11 , 12 ], as well as high reaction temperatures [ 14 ], harsh reaction conditions, long reaction times [ 15 ], and solubility issues [ 16 ], which can hamper the efficiency and scalability of the synthesis. Various strategies have been proposed for the enzymatic kinetic resolution of racemic atenolol, as well as for the enantioselective synthesis of the ( S )-enantiomer to which the maximum 1-blocking activity is attributed [ 17 , 18 , 19 , 20 , 21 ]. Although the efficient methods that lead to the formation of enantiomerically pure ( S )-atenolol can be of interest to the pharmaceutical industry and academia, the proposed routes use multistep procedures with a low overall yield, thus not aligning with the current environmental challenges [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%